A Rare Case: Primary Pulmonary Amyloidosis - Ceyda Ceylan; Gülay Turan; Arslan Hirad Gani; Mustafa Kuzucuoğlu (Düzce Tıp Fakültesi Dergisi)
Amyloidosis is a rare disorder characterized by the extracellular deposition of insoluble protein aggregates. There are two common types of amyloidosis: Amyloid A (AA) and amyloid light chain (AL). AA amyloidosis typically occurs secondary to chronic inflammatory processes such as tuberculosis and rheumatoid arthritis, with pulmonary involvement being a rare manifestation. AL amyloidosis, on the other hand, is often associated with conditions like multiple myeloma, gammopathies, and idiopathic primary amyloidosis. While kidney involvement is common, pulmonary involvement can also occur as part of systemic amyloidosis or, more rarely, in an isolated form. Pulmonary amyloidosis can present in three forms: nodular, diffuse, and tracheobronchial. This study presented a case of primary pulmonary amyloidosis in the nodular form, identified in a 69-year-old female patient.